Thrips dynamics in Allium crops: Unraveling the role of reproductive mode and weather variables in Thrips tabaci population development - Bettina Porta; Ben Vosman; Pablo González Barrios; Richard G. F. Visser; Guillermo A. Galván; Olga E. Scholten (PLoS ONE, 2025)
Thrips tabaci is the main thrips species affecting onion and related species. It is a cryptic species complex comprising three phylogenetic groups characterized by different reproductive modes (thelytoky or arrhenotoky) and host plant specialization. Thrips tabaci populations vary widely in genetic diversity, raising questions about the factor(s) that drive this diversity. We investigated the genetic diversity, reproductive mode, and heteroplasmy frequency in T. tabaci populations from different Allium spp fields in six locations in the Netherlands in 2021 and at two locations from the North and South of Uruguay over three years to unravel how the diversity is structured in the populations and if changes can be associated with weather variables. The thrips populations from each location studied were characterized by sequencing 33 individuals per sampling using the cytochrome oxidase subunit I (COI) gene. The reproductive mode was determined using specific primers and a phylogenetic analysis. Daily data for the weather variables was obtained from agrometeorological experimental stations located in the Uruguayan sampled crop fields. The diversity, reproductive mode, and heteroplasmy of T. tabaci populations in onion crops exhibited significant year-to-year variation depending on the location. Changes in the relative frequency of each reproductive mode in populations are associated with weather variables: precipitation, temperature, number of frosts, and relative humidity. Heteroplasmy frequency was associated with the same weather variables except temperature. In Uruguay and the Netherlands, T. tabaci thelytokous haplotype H1 was the most common, showing different heteroplasmy levels within and between the populations. In the field populations, a high frequency of heteroplasmic H1 individuals was associated with low precipitation, while all H1 individuals were also associated with high temperature and high relative humidity. In Uruguay, heteroplasmy was associated with arrhenotokous T. tabaci haplotypes, which were highly common in the North, pointing at specific adaptations leading to a faster population build-up. All this information may be instrumental for designing more precise integrated pest management techniques in both conventional and organic production.